Climate-human-landscape interaction in the eastern foothills of Mt. Kilimanjaro (equatorial East Africa) during the last two millennia. (April 2021) - van der Plas, Geert W; Rucina, Stephen M; Hemp, Andreas; Marchant, Robert A; Hooghiemstra, Henry; Schüler, Lisa; Verschuren, Dirk
The Mt. Kilimanjaro region is known for its long history of intensive agriculture, but the temporal extent of human activity and its impact on the regional ecosystem are not well known. In this study, climate-human-landscape interactions during the past ~2200 years were examined using climate and vegetation proxies extracted from the continuous and high-resolution sediment record of Lake Chala. Ancient-to-modern regional human activity is documented against a backdrop of long-term vegetation dynamics in the low-elevation savanna woodland southeast of Mt. Kilimanjaro and riparian forest within Chala crater. During prolonged dry periods (~1170–1300 CE), succulent dry crater forest expanded relative to the moist lakeshore forest. The savanna landscape surrounding Chala crater was relatively stable through time, except that savanna grasses were stimulated by higher precipitation, consistent with the fuel-limited fire regime evidenced in the charcoal record. Expansion of subalpine ericaceous vegetation and a general decline in Afromontane forest taxa on Mt. Kilimanjaro after 550 CE may reflect a lowering of its upper forest line. The earliest robust signature of human influence on regional vegetation involves an increase in ruderal (weedy) plant taxa around 1100 CE, possibly associated with the development of Chagga homegardens and associated agroforestry in the submontane forest zone. A first hint of cereal agriculture (likely sorghum) is observed around 1550 CE, followed by a more robust signature from 1780 CE onwards which likely reflects the start of lowland irrigation agriculture. From 1780 CE we also find the first undisputed appearance of maize, introduced to East Africa about a century earlier.